Association of anti-tuberculosis drug concentrations in hair and treatment outcomes in MDR- and XDR-TB. Issue 2 (26th April 2019) - Metcalfe, John; Bacchetti, Peter; Gerona, Roy; Esmail, Ali; Dheda, Keertan; Gandhi, Monica
Anti-tuberculosis drug concentrations in hair, a non-biohazardous and noninvasively collected biomatrix, predict extensively drug-resistant-TB clinical outcomes in a high-burden setting. http://ow.ly/80xi30o8qSa Therapeutic drug monitoring for drug-resistant tuberculosis (TB) is likely to improve treatment outcomes. While assessments of plasma drug levels can explain pharmacokinetic variability among trial participants, these measures require phlebotomy and a cold chain, and are generally not repeated frequently enough to characterise drug exposure over time. Using a novel multi-analyte assay, we found evidence that higher anti-TB drug concentrations in hair, a non-biohazardous and noninvasively collected biomatrix, predict extensively-drug resistant-TB clinical outcomes in a high-burden setting.